IMPACT OF SOCIAL CHANGE ON SOCIETY FROM THE CRIME OF CORRUPTION - Nandha Risky Putra; Rosa Linda (Komisi Pemberantasan Korupsi, 2022)
Corruption in Indonesia has threatened all aspects of social, national, and state life. Corruption has also brought enormous material losses to state finances regarding economy, society, and culture. Moreover, the corruption act prompted inevitable social changes due to crime. The main concern in this article is to perceive and analyze the social development related to the corruption act. The article furthermore highlights the measure taken by Indonesia's government to overcome such an impact on society caused by the presence of corruption acts. The method used in this article is normative legal research, which is prescriptive analytical, through a conceptual, a statute, and a case approach in assessing community participation in efforts to prevent corruption. The result of this study shows that corruption fosters the decline in social welfare, compelling the broad society to be afflicted by these irresponsible behaviors conducted by the corruptors. In this regard, the government is encouraged to encounter efforts to involve public participation in optimizing the prevention of corruption acts. This effort includes the direction to increase public awareness, step actions, and procedural motions that the community can perform in overcoming corruption acts.